Respon Wajib Pajak Terhadap Surat Permintaan Penjelasan Data dan/atau Keterangan (SP2DK) - Sherly Rivani; Charoline Cheisviyanny (Jurnal Eksplorasi Akuntansi, 2023)
This study aims to analyze the taxpayer’s point of view about SP2DK. This study uses a qualitative method with a phenomenological approach. Data collection techniques using observation and semi-structured interviews. This research is different from previous research because in this this research, SP2DK will be explored in depth and the respondents in this study are taxpayers who have received SP2DK. The results of the study revealed that there were differences in the taxpayer’s point of view about SP2DK, the responses were positive, neutral and negative about the SP2DK received. For the further researchers, it is better to use a wider scope and include all groups of taxpayer.